Genome Wide Analysis of Fatty Acid Desaturation and Its Response to Temperature. Issue 3 (20th January 2017) - Menard, Guillaume N.; Moreno, Jose Martin; Bryant, Fiona M.; Munoz-Azcarate, Olaya; Kelly, Amélie A.; Hassani-Pak, Keywan; Kurup, Smita; Eastmond, Peter J.
Abstract : The polyunsaturated fatty acid content of Arabidopsis seeds is determined by both cis-acting variants in FATTY ACID DESATURASE2 and an independent temperature-responsiveness locus on chromosome 2. Abstract: Plants modify the polyunsaturated fatty acid content of their membrane and storage lipids in order to adapt to changes in temperature. In developing seeds, this response is largely controlled by the activities of the microsomal ω-6 and ω-3 fatty acid desaturases, FAD2 and FAD3. Although temperature regulation of desaturation has been studied at the molecular and biochemical levels, the genetic control of this trait is poorly understood. Here, we have characterized the response of Arabidopsis ( Arabidopsis thaliana ) seed lipids to variation in ambient temperature and found that heat inhibits both ω-6 and ω-3 desaturation in phosphatidylcholine, leading to a proportional change in triacylglycerol composition. Analysis of the 19 parental accessions of the multiparent advanced generation intercross (MAGIC) population showed that significant natural variation exists in the temperature responsiveness of ω-6 desaturation. A combination of quantitative trait locus (QTL ) analysis and genome-wide association studies (GWAS) using the MAGIC population suggests that ω-6 desaturation is largely controlled by cis-acting sequence variants in the FAD2 5′ untranslated region intron that determine the expression level of the gene. However, the temperature responsiveness of ω-6 desaturation is controlled by a separate QTL on chromosome 2. The identity of this locus is unknown, but genome-wide association studies identified potentially causal sequence variants within ∼40 genes in an ∼450-kb region of the QTL .